A Pilot Randomized Controlled Trial of Brief Cognitive-Behavioral Therapy for Anxiety in Patients with Terminal Cancer - Greer, Joseph A. (AlphaMed Press, 2012)
INTRODUCTION. Patients with terminal cancer often experience marked anxiety that is associated with poor quality of life. Although cognitive-behavioral therapy (CBT) is an evidence-based treatment for anxiety disorders, the approach needs to be adapted to address realistic concerns related to having cancer, such as worries about disease progression, disability, and death. In this pilot randomized controlled trial (clinicaltrials.gov identifier NCT00706290), we examined the feasibility and potential efficacy of brief CBT to reduce anxiety in patients with terminal cancer. METHODS. We adapted CBT by developing treatment modules targeting skills for relaxation, coping with cancer worries, and activity pacing. Adults with incurable malignancies and elevated anxiety based on the Hamilton Anxiety Rating Scale (HAM-A) were randomly assigned to individual CBT or a waitlist control group. Primary outcomes included the number of completed CBT visits and the change in HAM-A scores from baseline to 8-week follow-up per a treatment-blind evaluator. The feasibility criterion was 75% adherence to the intervention. RESULTS. We randomized 40 patients with terminal cancers to CBT (n = 20) or waitlist control (n = 20) groups; 70% completed posttreatment assessments. Most patients who received CBT (80%) participated in at least five of the required six therapy sessions. Analysis of covariance models, adjusted for baseline scores, showed that those assigned to CBT had greater improvements in HAM-A scores compared to the control group, with an adjusted mean difference of –5.41 (95% confidence interval: –10.78 to –0.04) and a large effect size for the intervention (Cohen's d = 0.80). CONCLUSION. Providing brief CBT tailored to the concerns of patients with terminal cancer was not only feasible but also led to significant improvements in anxiety.